A Comparative Study of Anti-rectangular AG-groupoids and Commutative Semigroups - Ahmad, I.; Rauf, A.; Khan, M. (The Nucleus, 2020)
In this paper, anti-rectangular AG-groupoids are studied. Some properties of anti-rectangular AGgroupoid are investigated via a concise study of its super classes. Furthermore, various conditions are explored under which an anti-rectangular AG-groupoid becomes commutative and hence a commutative semigroup. Alternatively, the paper is a pleasant contribution to the theory of commutative semigroups. Moreover, using the latest computational techniques of Prove-9 and Mace-4 a variety of examples and counterexamples are provided to depict various produced results.